Climate Change Sustainable Net-Zero Emissions by Uptake Atmospheric Carbon Dioxide by Terrestrial and Aquatic Plants - Bruce R. Hodgson (Journal of Weather Changes, 2026)
A sustainable global net-zero carbon emission is when emissions are equivalent to the uptake of carbon by global terrestrial and aquatic plants. To meet that objective, an approximate 50% reduction of fossil-fuel emissions was estimated for net-zero by 2050 using carbon dioxide concentrations and mass emission monitoring by NOAA and related references. From that data, the initial target level of reduction to obtain net-zero was selected for year 2000 to minimise effects of climate change on environmental damage. The recent finding that about half global emissions are taken up from the atmosphere and increases global terrestrial and aquatic plant growth, including agriculture plants for food production, indicates it is important to maintain the year 2000 levels in the atmosphere. It was concluded as renewable energy was found to need support, it could be supplemented by electricity production remaining after obtaining net-zero, which also supports the atmospheric carbon dioxide levels for their important global ecological contribution.
Keywords: Net-Zero Emissions